Economic Crisis in a Shortage Economy - Osband, Kent (Journal of Political Economy, 1992)
It is not unusual for reforming socialist economies to relax wage controls without hardening budget constraints on enterprises or freeing consumer goods prices. This policy can be dangerously destabilizing. While higher wages permit workers to purchase more of some goods, they also tend to exacerbate shortages and to breed waste and corruption. Beyond a certain level, economywide wage hikes will worsen worker welfare. This is true regardless of whether deficit goods are strictly rationed, are sold randomly at official prices to queuing workers, or are offered to workers by "insiders" only at black-market prices. However, the form of allocation does influence the levels of output and welfare.